The Relation Between Some Bio – Kinematic Variables According to Performance Phases Using 45˚Angle Jump Shot Accuracy in Women’s National Basketball League - Mawlood, Talar Bilal; Sadiq , Diar Mohammad (Journal of Physical Education, 2022)
The importance of the study lies in finding a numerical value for decrease or increase in body joints angles, angular speed, ball height, and shooting accuracy indicator in some bio – kinematical variables in female players of the national basketball league. These values will help overcome weaknesses and reinforce strengths in players during jump shot from 45˚ angle. The researchers used the descriptive method wit correlation relationships on (7) female players of the national Basketball league. The data was collected and treated using SPSS to conclude that all correlations were insignificant expect wrist angle during flexion, and head angle during rising, head angle and angular speed of the knee during flight and ball release. In addition to that, there was a significant correlation in vertical distance, resultant distance, and vertical distance of jump shooting from 45˚.